Pewarisan Tanah Minangkabau dalam Ilmu Fara’idh (Hukum Waris Islam); Dialog, Negosiasi, Pola Interaksi dan Dinamika antara Adat Minangkabau dan Agama - Faiz Badridduja; Indeska Putra; Fendi Agus Syaputra (Journal of Contemporary Law Studies, 2026)
The purpose of this study is to analyze the Minangkabau community's practices regarding land inheritance in West Sumatra based on applicable customary law and to explain the dynamics of these practices in relation to Islamic inheritance law or to describe them using Imam al-Syathibi's Maqashid Syari'ah theory, which is claimed to be an Islamic perspective. This study uses a qualitative method with a social integration paradigm and sociology of religion approach. Data collection was carried out through observation and interviews in three districts in West Sumatra, namely Padang Pariaman, Lima Puluh Kota, and Agam, as well as a literature and document study process related to the discussion in this study. Meanwhile, the type or nature of this article is descriptive narrative. The results of this study are that the Minangkabau land inheritance system, with the dualism of high and low pusako assets, can be integrated with faraid law through the perspective of Al-Syathibi's maqashid syari'ah. This approach ensures that the objectives of sharia, especially safeguarding assets (hifz al-mal) and descendants (hifz al-nasl), are fulfilled while maintaining Minangkabau cultural identity. By utilizing the principles of mashlahah and ijtihad maqashidi, this inheritance system can remain relevant in the modern era, supporting social justice and cultural harmony.